Engineering ellipsoidal cap-like hydrogel particles as building blocks or sacrificial templates for three-dimensional cell culture - Zhang, Weiwei; Huang, Guoyou; Ng, Kelvin Wei Shan; Ji, Yuan; Gao, Bin; Huang, Liqing; Zhou, Jinxiong; Lu, Tian Jian; Xu, Feng (Royal Society of Chemistry, 2018)
Hydrogel particles that can be engineered to compartmentally culture cells in a three-dimensional (3D) and high-Throughput manner have attracted increasing interest in the biomedical area. However, the ability to generate hydrogel particles with specially designed structures and their potential biomedical applications need to be further explored. This work introduces a method for fabricating hydrogel particles in an ellipsoidal cap-like shape (i.e., ellipsoidal cap-like hydrogel particles) by employing an open-pore anodic aluminum oxide membrane. Hydrogel particles of different sizes are fabricated. The ability to produce ellipsoidal cap-like magnetic hydrogel particles with controlled distribution of magnetic nanoparticles is demonstrated. Encapsulated cells show high viability, indicating the potential for using these hydrogel particles as structure-and remote-controllable building blocks for tissue engineering application. Moreover, the hydrogel particles are also used as sacrificial templates for fabricating ellipsoidal cap-like concave wells, which are further applied for producing size controllable cell aggregates. The results are beneficial for the development of hydrogel particles and their applications in 3D cell culture.